Environmental Disasters and Migration - Linguère Mously Mbaye; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2015)
This paper reviews the effect of environmental disasters on migration. Although there is an increase of environmental disasters and migration over the past years, the relationship is complex. While some authors find that environmental disasters increase migration, others show that they have only a marginal or no effect or are even negative. Migration appears to be an insurance mechanism against environmental shocks. Remittances help to decrease households' vulnerability to shocks but also dampen their adverse effects. Finally, we discuss policy implications and future research avenues.
Keywords: J61; O15; Q54; Q56; 330; environmental shocks; forced migration; remittances; migration as insurance; floods; earthquakes; droughts